A note on the effect of phosphorus on the microstructure and mechanical properties of leaded-tin bronze - Aksoy, M; Kuzucu, V; Turhan, H (Elsevier Science Sa, 2002)
In this study, the effect of phosphorus on microstructure and mechanical properties of leaded-tin bronze was investigated by using scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction techniques, and tensile, fatigue and adhesive wear tests. It was observed that phosphorus prevented the growth of (Zn, Cu)S, which is a brittle and undesirable phase, by surrounding its environment, and therefore it increased the fatigue life and tensile strength of the material significantly, but it decreased the wear resistance of the material by increasing the mass loss at the initial stage of wear. It was concluded that the leaded-tin bronzes containing phosphorus can be preferred in manufacturing machine elements in which fatigue life is important. (C) 2002 Published by Elsevier Science B.V.
Keywords: leaded-tin bronze; microstructure; mechanical properties